PROPOSAL DESIGN OF PROGRAM EVALUATION: PROPOSAL DESAIN EVALUASI PROGRAM - Rivan Ardi Yuniangga (SOSIOEDUKASI, 2020)
This research is the result of observations made by researchers at SMA Muhammadiyah 2 Genteng Banyuwangi. This research is related to several evaluation programs implemented in schools. Every evaluation program definitely needs a proposal that is used to build an implemented evaluation program. The method used in this research is descriptive qualitative. The data obtained were then presented in the form of words and narratives which were presented in depth. The informants in this study were from several school elements ranging from educators, education personnel and other employees. Determination of informants in this study is by purposive sampling where the researcher determines and chooses first who the informants are to support the compilation of this research report. The results obtained from this research are that with the existence of a proposal, every activity carried out will feel more helpful and light because the proposal can be used as a forum to convey meanings and objectives. In addition, proposals are also used to clarify and distinguish some of the elements contained in the activity, starting from the title, meaning and purpose, core and closing.